Risk of sleep problems in a clinical sample of children who stutter - Couto, Maria Clara Helena do [UNESP]; Canhetti de Oliveira, Cristiane Moço [UNESP]; Merlo, Sandra; Briley, Patrick M.; Pinato, Luciana [UNESP] (Elsevier, 2024)
Purpose: Previous studies have shown increased prevalence of sleep problems among people who stutter. However, there is a lack of knowledge about what these sleep problems may specifically be. Method: Fifty children who stutter (CWS) from 6;0 to 12;9 years of age and 50 age- and gender-matched controls participated in this study. Parents did not report coexisting conditions, excepting stuttering and/or sleep problems. Sleep problems were investigated using a standardized questionnaire answered by parents. The questionnaire shows cut-off scores to identify the risk of sleep problems as a whole and on each one of the six subscales (i.e., disorders of initiating and maintaining sleep; sleep breathing disorders; disorders of arousal; sleep-wake transition disorders; disorders of excessive somnolence; and sleep hyperhidrosis). Scores above the cut-off are suggestive of sleep problems. Results: Twenty-one CWS scored higher than the cut-off on the sleep questionnaire compared to only two controls (p < 0.00001). Specifically, CWS scored higher than controls in disorders of initiating and maintaining sleep, sleep-wake transition disorders (especially jerking, sleep talking, and bruxism), and disorders of excessive somnolence (p < 0.0083, corrected for multiple comparisons). Discussion: Compared to controls, CWS are at greater risk for sleep problems, which are not consequences of coexisting disorders. Present findings confirm and expand current knowledge about sleep problems in CWS. Directionality possibilities and clinical implications are discussed.
Keywords: Behavior; Children; Sleep; Speech-language; Stutter